Teaching Methods: The Advantages Of Using Method Comunicative Language Teaching For English Language - diantimarlina (UPT Perpustakaan Universitas Jambi, 2025)
This article examined the benefits of implementing the Communicative Language Teaching (CLT) method in English language instruction. CLT focused on fostering students' communicative competence by engaging them in interactive activities reflective of real-life scenarios. The method aimed to develop English proficiency holistically, addressing speaking, listening, reading, and writing skills in an integrated manner. The discussion included an overview of the foundational principles of CLT, its significant advantages, and practical approaches for applying the method in classroom settings. It highlighted how CLT encouraged student-centered learning, where learners actively participated in meaningful communication rather than passively absorbing information. Additionally, the article referenced recent research findings that demonstrated the method’s effectiveness in enhancing student engagement, increasing motivation, and building self-confidence in using English. These studies underscored how CLT not only improved linguistic skills but also created a dynamic and supportive learning environment, making the language acquisition process more relevant and enjoyable.